2006
DOI: 10.1002/asi.20464
|View full text |Cite
|
Sign up to set email alerts
|

Temporal analysis of a very large topically categorized Web query log

Abstract: Web queries that constituted the total query traffic for a 6-month period of a general-purpose commercial Web search service. Previously, query logs were studied from a single, cumulative view. In contrast, this study builds on the authors' previous work, which showed changes in popularity and uniqueness of topically categorized queries across the hours in a day. To further their analysis, they examine query traffic on a daily, weekly, and monthly basis by matching it against lists of queries that have been to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 27 publications
3
54
0
Order By: Relevance
“…Pu et al (2002) used a similar approach to develop their subject taxonomy for the automatic classification of web query terms into broad subject categories. Beitzel et al (2007) involved the analysis of the web query logs of the America Online (AOL) web search service. However, the authors used a longitudinal analysis "to examine static and topical changes [in querying] over longer periods such as days, weeks, and months" (Beitzel et al, 2007, p. 167).…”
Section: Rationale For the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Pu et al (2002) used a similar approach to develop their subject taxonomy for the automatic classification of web query terms into broad subject categories. Beitzel et al (2007) involved the analysis of the web query logs of the America Online (AOL) web search service. However, the authors used a longitudinal analysis "to examine static and topical changes [in querying] over longer periods such as days, weeks, and months" (Beitzel et al, 2007, p. 167).…”
Section: Rationale For the Studymentioning
confidence: 99%
“…A rather significant literature exists currently in information science that studies information seekers' queries submitted through various types of search engines (e.g., Beitzel, Jensen, Chowdhury, Frieder, & Grossman, 2007;Chau, Fang, & Sheng, 2005;Lau & Goh, 2006;Pu, Chuang, & Yang, 2002;Rieh & Xie, 2006;Ross & Wolfram, 2000;Silverstein, Henzinger, Marais, & Moricz, 1999;Spink, Wolfram, Jansen, & Saracevic, 2001;Wang, Berry, & Yang, 2003). However, the published web search literature lacks the analysis of large amounts of unobtrusively collected data such as those found in web logs to determine the types of information sought through government websites in general, and municipal government websites particularly.…”
Section: Introductionmentioning
confidence: 97%
“…The intuition is that pages on which users spent more time are more relevant than pages that users leave very quickly. The authors of [3] analyzed an AOL query log in terms of how the query behavior of users changes over time. They found that certain topical categories can exhibit both short-term, i.e.…”
Section: Related Workmentioning
confidence: 99%
“…Beitzel's study focused on investigating the nature of changes in the query stream of a very large search service over. He also proposed a method of temporal log analysis that can be used to study changing topical trends over time in addition to the traditional static analysis [7]. Silverstein et al found that for 85% of the queries in Alta Vista only the first result screen is viewed, and 77% of the sessions contain only 1 query [8].…”
Section: B Research On Website Usage and Web Logsmentioning
confidence: 99%